An Empirical Investigation of the Impact of Covid-19 Pandemic on University Students - (:unkn) unknown (My University, 2022)
The purpose of this study is to examine the psychological consequences of COVID-19 pandemic on the current attitudes, behaviours, and future expectations of Gen Z as the upcoming generation of the business life. Data were gathered through an online survey during lockdown. The sample consists of 299 undergraduate students studying business major. Findings revealed that the respondents are hopeful about the future despite the pandemic. However, the female respondents feel less secure and more pessimistic in terms of the new normal conditions. Results also revealed that they tend to take more actions to the unknown future. Further recommendations are also provided.
Keywords: covid-19; future expectations; gen z; gender differences